Identification of IRF8, TMEM39A, and IKZF3-ZPBP2 as susceptibility loci for systemic lupus erythematosus in a large-scale multiracial replication study (2012)
Systemic lupus erythematosus (SLE) is a chronic heterogeneous autoimmune disorder characterized by the loss of tolerance to self-antigens and dysregulated interferon responses. The etiology of SLE is complex, involving both heritable and environmental factors. Candidate-gene studies and genome-wide association (GWA) scans have been successful in identifying new loci that contribute to disease susceptibility; however, much of the heritable risk has yet to be identified. In this study, we sought to replicate 1,580 variants showing suggestive association with SLE in a previously published GWA scan of European Americans; we tested a multiethnic population consisting of 7,998 SLE cases and 7,492 controls of European, African American, Asian, Hispanic, Gullah, and Amerindian ancestry to find association with the disease. Several genes relevant to immunological pathways showed association with SLE. Three loci exceeded the genome-wide significance threshold: interferon regulatory factor 8 (IRF8; rs11644034; p meta-Euro = 2.08 × 10 -10), transmembrane protein 39A (TMEM39A; rs1132200; p meta-all = 8.62 × 10 -9), and 17q21 (rs1453560; p meta-all = 3.48 × 10 -10) between IKAROS family of zinc finger 3 (AIOLOS; IKZF3) and zona pellucida binding protein 2 (ZPBP2). Fine mapping, resequencing, imputation, and haplotype analysis of IRF8 indicated that three independent effects tagged by rs8046526, rs450443, and rs4843869, respectively, were required for risk in individuals of European ancestry. Eleven additional replicated effects (5 × 10 -8 < p meta-Euro < 9.99 × 10 -5) were observed with CFHR1, CADM2, LOC730109/IL12A, LPP, LOC63920, SLU7, ADAMTSL1, C10orf64, OR8D4, FAM19A2, and STXBP6. The results of this study increase the number of confirmed SLE risk loci and identify others warranting further investigation. © 2012 The American Society of Human Genetics.